Integration of Transcriptome Resequencing and Quantitative Proteomics Analyses of Collagenase VII-Induced Intracerebral Hemorrhage in Mice - Cao, Fang; Guo, Yu; Zhang, Qiang; Fan, Yinchun; Liu, Qian; Song, Jiancheng; Zhong, Hua; Yao, Shengtao (Frontiers in Genetics, 2020)
Objective: Intracerebral hemorrhage (ICH) is a subtype of stroke, with high mortality and morbidity. Our aim was to comprehensively analyze transcriptome and proteome in an experimental ICH model. Methods: All mice were divided into ICH model (n=3) and sham groups (n=3). ICH was induced by collagenase VII. The ipsilateral hemisphere was used for whole transcriptome and proteomics resequencing. After preprocessing, differentially expressed lncRNAs (DElncRNAs), mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and DEproteins between ICH and sham groups were identified. Functional enrichment analysis was performed using the clusterProfiler package, followed by Protein-Protein Interaction (PPI) analysis. After that, the Pearson correlation coefficient between DEmRNAs and DElncRNAs or between DEmRNAs and DEproteins was calculated. DElncRNAs with similar functions were analyzed by the GOSemSim package. After prediction of DEmiRNA-DEmRNA and DElncRNA-DEmiRNA relationships, a competing endogenous RNA (ceRNA) network was constructed. Several DEmRNAs and DElncRNAs were validated in ipsilateral hemisphere tissues of ICH model and control groups using RT-qPCR and western blot. Results: 31 DElncRNAs, 367 DEmRNAs, 35 DEmiRNAs and 96 DEproteins between ICH groups and sham groups were identified. DEmRNAs were mainly enriched in inflammation, such as cytokine-cytokine receptor interaction, IL-17 and TNF signaling pathways. A PPI network of DEmRNAs was constructed and hub genes were identified such as IL6 (degree=59), TNF (degree=44) and CXCR2 (degree=39). 24 DElncRNAs with similar functions were identified, including 15 up- and 9 down-regulated lncRNAs. After integration of DEmiRNA-DEmRNA and DElncRNA-DEmiRNA relationships, we constructed a ceRNA network, composed of 71 DEmRNAs, 17 DEmiRNAs and 12 DElncRNAs. RT-qPCR and western blot results confirmed that C3, Fga, and Slc4a1 proteins were lowly expressed and Penk was highly expressed in ICH than control groups, which could become potential markers for ICH. Conclusion: Our findings identified ICH-related DE-RNAs and proteins and potential molecular mechanisms of ICH by transcriptome resequencing and quantitative proteomic analyses.